Engaging Students Using Evidence to Promote Student Success - Kuh, George; Strydom, Francois; Loots, Sonja (UJ Press, 2017)
The book provides a rich, informative picture of the current state of student engagement evaluation, while also highlighting challenges and opportunities for future advances. A particular strength of this publication is its emphasis on the importance of taking evidence-based decisions, and showing how the South African Survey of Student Engagement (SASSE) can provide the evidence for well-informed changes in policy and practice in order to enhance student success." - Prof Magda Fourie-Malherbe, Stellenbosch University